PPP-BOTDA Distributed Optical Fiber Sensing Technology and Its Application to the Baishuihe Landslide - Zhao, Meng; Yi, Xianlong; Zhang, Junrong; Lin, Chengyuan (Frontiers in Earth Science, 2021)
Serious landslide hazards are prevalent along the Yangtze River in China, particularly in the Three Gorges Reservoir area. Thus, landslide monitoring and forecasting technology research is critical if landslide geological hazards are to be prevented and controlled. Pulse-prepump brillouin optical time domain analysis (PPP-BOTDA) distributed optical fiber sensing technology is a recently developed monitoring method with evident advantages in precision and spatial resolution. Herein, fixed-point immobilization and direct burying methods were adopted to arrange parallel distribution of the strain and temperature-compensated optical fibers along the Baishuihe landslide’s front edge, in order to carry out ground surface deformation monitoring. The strain data acquired from both optical fibers were processed with temperature compensation to obtain the actual optical fiber strain produced by deformation. Butterworth low-pass filter denoising method was employed to determine the filter order (n) and cut-off frequency (Wn). The area differences between the two optical fiber monitoring curves and the fixed horizontal axis were selected as evaluation indexes to obtain the area difference along the optical fiber. This data were then leveraged to determine the positive correlation between the area difference and the optical fiber strain variation degree. Finally, these results were compared with the GPS and field measured data. This study shows that when PPP-BOTDA technology is used for landslide surface deformation monitoring in conjunction with Butterworth filter denoising and strain area difference, the optical fiber strain variation degree analysis results are consistent with the GPS monitoring data and the actual landslide deformation. As such, this methodology is highly relevant for reducing the workload and improving the monitoring precision in landslide monitoring, which in turn will protect lives and property.